PENGARUH PEMBERIAN PUPUK ORGANIK CAIR DARI TUMBUHAN BABADOTAN (Ageratum conyzoides L.)TERHADAP PERTUMBUHAN TANAMANSAWI PAKCOY (Brassica chinensis L.) - Harry Aprileo; Pitri Handayani; Leni Marlina (Pendidikan Biologi STKIP YPM Bangko, 2020)
This research was motivated by the problem of Babadotan plant weeds in oil palm plantations in Kabupaten Merangin . Babadotan plant has the potential as a liquid organic fertilizer. This research aims to determine the effect of liquid organic fertilizer from babadotan plants on the growth of pakcoy. This study used a one-factor completely randomized design (CRD), consisting of 6 treatments, namely P0 (0%), PI (10%), P2 (15%), P3 (20%), P4 (25%), P5 (30 %), with 4 repetitions. The growth parameters observed were the number of leaves, leaves surface area, plant height, and root length. Data were analyzed using analysis of variance and continued with the Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that the liquid organic fertilizer of babadotan plant had a very significant effect on leaf surface area, had a significant effect on root length, but did not significantly influence the growth of stem height and number of pakcoy leaves. Liquid organic fertilizer from babadotan plants with a concentration of 20% gives the highest average in each treatment for each measurement parameter. However, the best POC concentration from the results of the Duncan test showed that the treatment that had a significant effect on the leaf surface area and root length of the pakcoy plant was a concentration of 0% or without treatment.